The Relation between the Plasma Concentrations of Long-Acting Atypical Antipsychotics and Clinical Effectiveness in Patients Affected by Schizophrenia or Schizoaffective Disorder: A Comprehensive Overview - Capuzzi, Enrico; Ceresa, Alessandro; Caldiroli, Alice; Esposito, Cecilia M.; Ossola, Paolo; Buoli, Massimiliano (Current Pharmaceutical Design, 2021)
Atypical antipsychotic depot medications are currently recommended for patients with schizophrenia (SCZ) to prevent relapse and ameliorate the long-term prognosis of these patients. This review critically summarizes the available data about the association between the plasma concentrations of long-acting Second- Generation Antipsychotics (SGAs) and the clinical effectiveness of these compounds in patients affected by SCZ or schizoaffective disorder. Our question is if the measurement of these concentrations can be helpful for clinicians in predicting treatment response and clinical stabilization of patients. Bibliographic research on the main databases was performed, and 13 studies were finally included in this review. Contrasting results were found between plasma concentrations of long-acting injectable (LAI) risperidone and clinical amelioration according to rating scale scores. Data are too scanty to draw conclusions for olanzapine and paliperidone. In contrast, despite small sample sizes, data are quite concordant in showing a relation between long-acting SGA plasma concentrations and D2 receptor occupancy. Despite the preliminary encouraging results, particularly for D2 receptor occupancy, future research with larger samples will have to confirm the clinical usefulness of measuring LAI SGA plasma concentrations to predict the clinical response of patients affected by severe mental conditions such as SCZ.
Keywords: schizophrenia (SCZ)